Numerical analysis of embankment on soft soils with different / Rohamezan Rohim - Rohim, Rohamezan (Universiti Teknologi MARA Cawangan Pulau Pinang, 2003)
The problem related to the soft soils deposits is an important role in geotechnical works. Soft soil is very porous and fully saturated in nature. The degree of compressibility is high and low in undrained shear strength due to high amount of moisture content. With the existing equipment, engineers sometime forget or neglect the effect caused by the soft soils. The main problem faced by the structure built on the soft soil such as embankment, excavation and tunnel is the effect of time dependent deformation (during primary and secondary consolidation). Soft Soil Creep Model (SSC) and Soft Soil Model (SS) are standard models that are available in PLAXIS. Another two new models are Multilaminate Creep Model (MLC) and Multilaminate Soft Soil Model (MSS). These models were developed recently in the Institute of Geotechnical Engineering, University of Stuttgart. Simulations were conducted to investigate the horizontal and vertical displacements under specified loadings. MSS model shows higher settlement and horizontal displacement after the construction of embankment with 0.32m and 0.06m respectively. MLC model on the other hand shows the highest settlement and horizontal displacement with 2.4m and 0.25m respectively.